2003
DOI: 10.1080/01485010390129296-1
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-Related Enzymes in Cell Cultures From Different Regions of Human Epididymis

Abstract: Protection of maturing sperm from potential endogenous or exogenous harmful substances during their transit throughout the epididymis is a critical event. The authors studied the activity of gamma-glutamyl transpeptidase (GGT) and glutathione S-transferase (GST), and glutathione (GSH) levels in epithelial cell cultures from human caput, corpus, and cauda epididymides. Tissue was obtained from patients undergoing therapeutic orchidectomy for prostatic cancer. Enzymatic activity was measured in conditioned media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
2
3
1
Order By: Relevance
“…Finally, together with thioredoxins and peroxiredoxin 3, we have found that glutathione-S-transferases (GSTπ and GSTµ) are also significantly up-regulated both in the caput and cauda epididymidis compartments of the double mutant animals. This agrees with previous reports showing that GSTs are expressed at significant levels in mammalian epididymis [31], [42]. Induced expression of multiple forms of GST appears to be an evolutionary response of cells to protect against chemical toxicity and oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, together with thioredoxins and peroxiredoxin 3, we have found that glutathione-S-transferases (GSTπ and GSTµ) are also significantly up-regulated both in the caput and cauda epididymidis compartments of the double mutant animals. This agrees with previous reports showing that GSTs are expressed at significant levels in mammalian epididymis [31], [42]. Induced expression of multiple forms of GST appears to be an evolutionary response of cells to protect against chemical toxicity and oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
“…The opposite has been reported for the GPx5 in the rat and mouse, in which the gene is expressed mainly in the initial segment and caput epididymis [6,8]. We have found the same difference between rats and men in other GSH related enzymes [20], suggesting that the genetic regulatory mechanism, an influence of testicular factors (which are not present in cultured cells), may be different in both species. However, androgen control of human epididymal GPx activity seems to be similar to other species studied [7].…”
Section: Discussioncontrasting
confidence: 89%
“…Epididymis plays important roles in sperm maturation, motility, and storage (21). The activity of some detoxifying enzymes such as gamma-glutamyltranspeptidase (GGT) and glutathione S-transferase (GST) was detected in epithelial cell culture of human epididymis (22). In epididymis of male Nrf2-knockout mice, lipid peroxidation increased, and expression of GST, sod2, and enzymatic activities of glutathione reductase and glutathione peroxidase decreased (9).…”
Section: Discussionmentioning
confidence: 99%